Sophaloseedlines A—G: Diverse Matrine‐Based Alkaloids from Sophora alopecuroides with Potential Anti‐Hepatitis B Virus Activities. Issue 9 (26th July 2021) - Luo, Ding; Wu, Zhong‐Nan; Zhang, Ji‐Hui; Lin, Qiang; Chen, Neng‐Hua; Chen, Si; Tang, Qing; Zhan, Zhao‐Chun; Fan, Chun‐Lin; Li, Yao‐Lan; Wang, Guo‐Cai; Zhang, Yu‐Bo
Main observation and conclusion: Sophaloseedlines A—G (1—7), seven new matrine‐based alkaloids along with two known analogues, were isolated from the seeds of Sophora alopecuroides . The new structures were determined based on extensive spectroscopic data, electronic circular dichroism calculations, and X‐ray crystallography. Notably, sophaloseedline A (1) represents a novel rearranged 6(5→17)‐ abeo‐ matrine alkaloid featuring unprecedented highly constructed 7/6/5/6 tetracyclic fused ring skeleton. The hypothetical biosynthetic pathways for sophaloseedlines A—F were proposed based on co‐existing precursors. Additionally, all the isolated alkaloids were screened for their antiviral activities against hepatitis B virus, and new alkaloids 1 and 2 displayed more potent activities than those of matrine (a parent alkaloid of title plant) and positive control (lamivudine). Abstract : Sophaloseedlines A‐G (1—7), seven new matrine‐based alkaloids along with two known analogues, were isolated from the seeds of Sophora alopecuroides . The new structures were determined based on extensive spectroscopic data, electronic circular dichroism calculations, and X‐ray crystallography. Notably, sophaloseedline A (1) represents a novel rearranged 6(5→17)‐ abeo‐ matrine alkaloid featuring unprecedented highly constructed 7/6/5/6 tetracyclic fused ring skeleton. The hypothetical biosynthetic pathways for sophaloseedlines A—F were proposed based on co‐existing precursors. Additionally, all the isolated alkaloids were screened for their antiviral activities against hepatitis B virus, and new alkaloids 1 and 2 displayed more potent activities than those of matrine (a parent alkaloid of title plant) and positive control (lamivudine).